IMPROVING TENTH-GRADE STUDENTS’ WRITING SKILLS BY USING THE OUTLINING TECHNIQUE AT SECONDARY SCHOOL IN LAMPUNG - Ranggi Dewi Adelia Putri; Achmad Yudi Wahyudin (Universitas Wiralodra, 2025)
This research investigates the impact of an outlining strategy on improving students' descriptive writing skills. A mixed-methods approach was used, with a quasi-experimental design in two classes and qualitative interviews. Data were collected through pretests, treatment, and post-tests. The research involved two samples of tenth graders: the experimental group (33 students) and the control group (34 students). Post-test results revealed an average score of 69.82 for the experimental group and 62.41 for the control group. The experimental group showed a gain of 16.82 points compared to 7.18 points in the control group, with a t-observe value of 5.197, exceeding the t-table value of 1.670. The findings highlight challenges in writing descriptive texts, such as limited grammar and vocabulary knowledge, difficulties in sentence construction, and low enthusiasm for learning. Outlining helps students focus on idea development, plan paragraph structures, expand vocabulary, and refine grammar in later drafts. Teachers play a critical role in motivating students by providing appropriate challenges, celebrating achievements, and using engaging teaching methods like games and discussions. With well-trained, enthusiastic teachers, students can build confidence, find learning enjoyable, and improve their English skills effectively.